Применение теории конечных автоматов в разработке программных систем - Смирнова, Н. В.; Смирнов, В. В.; Смірнова, Н. В.; Смірнов, В. В.; Smirnova, Nataliya; Smirnov, Vladimir (КНТУ, 2014)
Приведено решение задачи устранения неоднозначностей в работе конечного автомата при создании управляющих программных систем. Создана структурная схема модели конечного автомата с учетом времени ожидания выполнения функций и результата их выполнения, подсчета количества событий и стека состояний. Наведено рішення задачі усунення неоднозначностей в роботі кінцевого автомата при створенні керуючих програмних систем. Створена структурна схема моделі кінцевого автомата з урахуванням часу очікування виконання функцій і результату їх виконання, підрахунку кількості подій і стека станів. The purpose of this article is the solution to eliminate the finite state machine ambiguities when creating control software systems. Created a block diagram of a finite automaton model with the time to wait for the functions results and their implementation, counting the number of events and status stack. The model combines the advantages of an event object-oriented technology and the SWITCHprogramming technology. The resulting model is the basis of the base class machine that is used in the process of creating software systems for management of the facility.
Застосування теорії кінцевих автоматів у розробці програмних систем
The finite state machine theory in developing software systems application
Keywords: конечный автомат; класс; SWITCH-технология; объект управления; кінцевий автомат; клас; SWITCH-технологія; об'єкт управління; finite state machine; class; SWITCH-technology; controlled object